Pengaruh Citra Merek, Kualitas Dan Harga Terhadap Keputusan Pembelian Air Mineral Merek Aqua (Studi Pada Mahasiswa Universitas Muhammadiyah Surakarta) - Hidayati, Khafsoh Nur, Ir. Irmawati, S.E., M.M (2017)
In the process of purchasing decisions marketers should be explore the various impact on buyers and developing the understanding of how consumers make their purchasing decisions. This research aims to determine the effect of brand image, product quality and price of the purchase decision. The population in this study were students that consume Aqua mineral water brand at Muhammadiyah University of Surakarta. This Research uses a quantitative research, the data collection methods using a questionnaire that filled directly by the respondents, the consumer of Aqua mineral water brand. The test in this study using SPSS version 16. In a linear multiple regression analysis, known that the variable Brand image, Product Quality and Price has positive significant effect on the purchase decision. T test results of the Brand, Product Quality and Price obtained sig. < 0.05, partially independent variables positive effect on the dependent variable is received. F test showed that all variables independently has positive effect on the dependent variable was received. Determination of coefficient (R2) shows that Brand, Product Quality and Price were able to influence the purchase decision Aqua mineral water by 70,6%, while the other was explained by variables outside of this research.